Forensic vigilance and selective attention in forensic professionals: an initial empirical study. - Clercx, Maartje (Journal of Forensic Practice, 2026)
Purpose: The forensic mental health system constitutes a unique work environment. Forensic vigilance is often named as a core competency of forensic professionals, both in general and in relation to incident prevention. In both the definition and the model of forensic vigilance, observation is an important aspect, as the professional should observe their surroundings and note any signals of possible impeding danger or deterioration in mental state of patients; however, it has not been studied how some signals are observed, while others are ignored. This study aims to study whether forensic professionals have selective attention to notable changes in the environment or cues of patient distress. Design/methodology/approach: The author investigated whether scores on the Forensic Vigilance Estimate were related to selective attention in forensic mental health-care professionals by means of a video task based on the "invisible gorilla experiment" and a Dot Probe task. In total, 131 forensic psychiatric professionals completed the video task, and 50 forensic psychiatric professionals completed the Dot Probe task. Findings: No significant relationship between forensic vigilance and selective attention was found, neither on the video task nor on the Dot Probe task. The author did find a negative relationship between performance on the video task and work experience in forensic mental health care. Practical implications: Possibly selective attention in the context of forensic vigilance pertains to cues of distress in patients known by the professionals. Originality/value: Though often hypothesized as important, to the best of the author's knowledge, this study represents the first effort to investigate the role of observation in forensic vigilance.